Molecular Identification and Phylogenetic Reconstruction of Horseshoe Crab (Xiphosura, Limulidae) from the East Java Region - Sapto Andriyono; Catlya Tasya Adella Tasya Adella; Mufasirin Mufasirin; Lailatul Lutfiyah; Heru Pramono; Nur Izzati Mohd Noh; Dwi Anggorowati Rahayu (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Horseshoe crabs, ancient marine arthropods of the Limulidae family, are currently facing significant threats due to overexploitation driven by high demand for their eggs, which are widely consumed, and their hemolymph, which is critical for biomedical applications. This study aims to evaluate the molecular identification and phylogenetic placement of horseshoe crabs in East Java, a region previously unreported in this context. DNA barcoding was employed to analyze the mitochondrial COI gene region, complemented by detailed morphological identification, to provide a comprehensive understanding of the species in this area. A universal primer LCO/HCO was used for PCR, as described in a previous report, and Sanger sequencing was performed to confirm the approximately 655 bp amplification product. This research identifies horseshoe crabs from six distinct locations in East Java as Tachypleus gigas using molecular methods, with genetic analysis indicating>99% similarity to T. gigas sequences in the GenBank database. Morphological examinations of specimens from seven areas further corroborated the presence of T. gigas, distinguished by characteristic serrations along the telson and a single spine on the posterior region of the opisthosoma. The phylogenetic tree, constructed from our genetic data, shows that Tachypleus gigas populations in East Java are clustered in the same clade as those in Southeast Asia, as supported by GenBank records. This study underscores the importance of integrating genetic and morphological approaches for accurate species identification. Moreover, it provides crucial baseline data for developing conservation strategies to preserve Tachypleus gigas populations in East Java, thereby contributing to broader conservation efforts for this species.